Knowledge gaps and future directions in cognitive functions in children and adolescents with primary arterial hypertension: A systematic review - Lucas, Ignacio; Puteikis, Kristijonas; Sinha, Manish D.; Litwin, Mieczysław; Merkevicius, Kajus; Azukaitis, Karolis; Rus, Rina; Pac, Michał; Obrycki, Lukasz; Bårdsen, Tonje; Śladowska-Kozłowska, Joanna; Sagsak, Elif; et al. (Frontiers in Cardiovascular Medicine, 2022)
Arterial hypertension (AH) among adults is known to be associated with worse cognitive outcomes. Similarly, children and adolescents with AH could be expected to underperform during neuropsychological evaluations when compared with healthy peers. Our aims were to review the existing literature on cognitive functioning among children and adolescents with primary AH and to identify what additional evidence may be needed to substantiate the impact of hypertension on poor cognitive outcomes in this population. We conducted a systematic review of articles in PubMed and Web of Science published before 17 January 2022, reporting on cognitive testing among children and adolescents with primary AH. From 1316 records, 13 were included in the review – 7 used battery-testing while other employed indirect measures of cognitive functions. Most of the studies reported worse results among individuals with AH. Results of two prospective trials suggested that cognitive functioning may improve after starting antihypertensive treatment. Ambulatory blood pressure monitoring was shown to be more strongly related to cognitive testing results than office measures of blood pressure. Significant confounders, namely obesity and sleep apnoea, were identified throughout the studies. Our review indicates that evidence relating AH with poor cognitive functioning among youth is usually based on indirect measures of executive functions (e.g., questionnaires) rather than objective neuropsychological tests. Future prospective trials set to test different cognitive domains in children and adolescents undergoing treatment for AH are endorsed and should consider using standardized neuropsychological batteries as well as adjust the assessing results for obesity and sleep disorders.